Ergenlik ve Toplum - (:unkn) unknown (My University, 2002)
Ergenlik insan hayatının önemli ve zor bir gelişim evresidir, içinde yaşanılan çağ, bu gelişimi daha da karmaşık hale sokmaktadır. Ergenler pek çok yararlı ve zararlı etkiye açık olarak ve çoğunlukla tek başlarına büyümektedirler. Uyuşturucu kullanımı, yüksek suç oranlan, cinsellik ve cinsel hastalıklar, alkol, sigara içme, kazalar, ebeveynlerle iletişim problemleri, arkadaş baskılan, televizyon ve internetin gençler üzerindeki etkileri bu dönemin belli başlı problemleri arasındadır. Ergenlere yönelik geliştirilen pek çok programdan oldukça etkili sonuçlar elde edilmektedir. Ebeveynler, eğitimciler ve uzmanlar elbirliği ile gençlerin sağlıklı gelişimi için çabalamalıdır. Ergenlik döneminin özelliklerini bilmek ve ergenle iletişim kurmaya çalışmak önemlidir.

Adolescence is quite a difficult and important developmental period of human lifecycle. Today going through adolescence is much more difficult than it was in the past. Adolescents are under the influence of various positive and negative factors, and they are growing up on their own mostly. Some of the problems of this period can be listed as drug use and addiction, high rates of crime, sex, sexual diseases, alcohol, smoking, traffic accidents, communication problems with parents, peer group pressures, influence of television and Internet on adolescents. There are effective programs targeting adolescents. Parents, educators and professionals can bring up healthy adolescents by working cooperatively as a team. Adults need to be aware of the developmental characteristics of this period. They should also need to try to establish a healthy communication with their adolescent children.
Adolescence and Society
Keywords: İletişim